MEDIA INFORMASI CV SARINA MUARA BULIAN BERBASIS WEBSITE - Nurjani, Yeni (Lembaga Penelitian Dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2016)
Thesis titled Media Information Sarina Muarabulian CV âBased Website motivated by problems with the slow progress on the CV Sarina , giving rise to a new initiative of the owner of CV CV Sarina Sarina to introduce to the public. With the development of increasingly sophisticated technology , then the owner of an online promotional things look very appropriate . Given the problems tersebutlah , the author and owner of CV Sarina conduct mutual cooperation had a positive impact . In addition to being a media campaign making of this website also serves as a medium for online sales . Making this website using PHP as the programming language and MySQL as the database. So it is expected with this website , will be a solution for the CV Sarina to further expand its business . Data was obtained through field studies and literature.